N-heterocyclic carbenes : effective tools for organometallic synthesis - Nolan, Steven P. (Wiley-VCH, 2014)
"This comprehensive reference and handbook covers in depth all major aspects of the use of N-heterocyclic carbene-complexes in organic synthesis: from the theoretical background to characterization, and from cross-coupling reactions to olefin metathesis. Edited by a leader and experienced scientist in the field of homogeneous catalysis and use of NHCs, this is an essential tool for every academic and industrial synthetic chemist." --